2022
DOI: 10.1111/jce.15378
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Use for Recovery of advanced atrioVentricular block Immediately after VALvular surgery (SURVIVAL): A preliminary randomized clinical trial

Abstract: Background Atrioventricular block (AVB) is an important complication following valvular surgery. Several factors including inflammation‐mediated injury might trigger AVB. Methods Patients with advanced postoperative AVB were randomly assigned to receive either dexamethasone (0.4 mg/kg, maximum 30 mg/day) intravenously for 3 days or conservative care only. Primary endpoint was recovery rate in Day 5 since randomization. Secondary endpoints were recovery rate in Day 7 and Day 10, cumulative AVB time, permanent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Corticosteroids have a potent anti-inflammatory effect mediated by receptors that modulate the expression of inflammatory genes. The high antiedematous activity 11 of these drugs, as demonstrated in previous studies, 12,13 may prevent early conduction disturbances after valve implantation.…”
Section: Introductionmentioning
confidence: 69%
“…Corticosteroids have a potent anti-inflammatory effect mediated by receptors that modulate the expression of inflammatory genes. The high antiedematous activity 11 of these drugs, as demonstrated in previous studies, 12,13 may prevent early conduction disturbances after valve implantation.…”
Section: Introductionmentioning
confidence: 69%
“…In this issue, Ghodsi et al randomize those with AV block after valvular surgery to dexamethasone 4 mg/kg for 3 days or normal care 8 . Steroids, as the authors indicate, have been shown to reduce ischemia‐reperfusion injury, reduce inflammation and edema, and alter molecular/channel effects resulting in enhanced conduction.…”
Section: "To Do Nothing Is Also a Good Remedy"mentioning
confidence: 99%
“…4 In this issue, Ghodsi et al randomize those with AV block after valvular surgery to dexamethasone 4 mg/kg for 3 days or normal care. 8 Steroids, as the authors indicate, have been shown to reduce ischemia-reperfusion injury, reduce inflammation and edema, and alter molecular/channel effects resulting in enhanced conduction. The rationale for this intervention was to hasten the recovery or "unmask" reversibly-injured conduction tissue in hopes of enhancing clinical decisions for PM implantation in the future.…”
mentioning
confidence: 99%